Efeito dos tutores de madeira tratada com CCA-C na qualidade da pimenta-do-reino (Piper nigrum L.) cultivada no norte do estado do Espírito Santo - Rosa, Arlon Bastos da (2023)
The objective of the research was to analyze the effects of using wooden stakes treated with chromated copper arsenate, type C (CCA-C) on the quality of black pepper (Piper nigrum L.) cultivated in the north of the State of Espírito Santo. To evaluate the concentration of copper, chromium and arsenic elements, components of CCA-C, samples were collected from underground roots, green and mature fruits of plants aged 5; 7 and 13 years, plus the control (5-year-old plants, untreated wooden tutor). For the quantification of the elements, the material was dried, crushed and digested in a 2N hydrochloric acid (HCl) solution, and submitted to chemical analysis in mass spectrometry with inductively coupled plasma (ICP-MS/MS), using helium (He), as a collision gas. The results indicated that copper was found in higher concentrations in plants, being more adsorbed by underground roots, with a decrease in green and ripe fruits. Chromium behaved similarly to copper, and arsenic did not show differences between the analyzed ages, being with a concentration lower than that allowed by the Resolution of the Collegiate Board - RDC 26, June 2nd, 2015, of the Brazilian Health Ministry. For plants aged 5 and 7 years (treated tutors) copper concentration was observed above the maximum allowed. However, copper concentrations in mature fruits from plants aged 13 years were within acceptable values. Thus, fruits of different ages and plant staking must be mixed and homogenized in order to obtain a good quality product that can be consumed without major consequences to human health.